Answered

Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.

Solve the system using substitution.
x + 2y = -6
6x + 2y = 4
([?], [ ]


Sagot :

Answer:

(2,-4)

Step-by-step explanation:

2y=-x-6                                        2+2y=-6

y=-1/2x-3                                      2y=-8

6x+2(-1/2x-3)=4

6x-x-6=4

5x=10

x=2

y=-4

We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.